Soil organic matter and feeding the future : environmental and agronomic impact - Lal, R. (Boca Raton C R C press, 2022)
"Soil organic matter (SOM) is the primary determinant of soil functionality and is a source of numerous ecosystem services critical to human well-being and nature conservancy. This volume of Advances in Soil Sciences presents impacts of land use and soil management on soil organic carbon (SOC) dynamics and discusses how conservation through restorative land use and adoption of recommended management practices to create a positive soil-ecosystem carbon budget can increase carbon stock and soil health"--
Keywords: Soil science; Agronomy--Effect of environment on